Cancer risk assessment for crystalline silica to implement California's Hot Spots Act - Collins, J. F.; Marty, M. A. (Scandinavian Journal of Work, Environment & Health, 1995)
Crystalline silica has been identified as a probable human carcinogen. To assess the potential for adverse health effects due to environmental exposures to respirable crystalline silica, a quantitative estimate of carcinogenicity has been made using incidence data from three studies in which long-term silica inhalation caused lung tumors in rats. The uncertainties in risk assessment in general and in the risk assessment for silica in particular are discussed.
Keywords: carcinogen; multistage model; risk assessment; silica